Bimbingan Kelompok dengan Teknik Mind Mapping untuk Meningkatkan Pemahaman Studi Lanjut Siswa - Laras Panji Pambudi; Awalya Awalya (Journal of Education and Counseling (JECO), 2021)
The research objective was to determine the effectiveness of group guidance with mind mapping techniques to increase students' understanding of further studies. This type of research is experimental research. The research was conducted at SMP N 18 Purworejo class IX G Academic Year 2020/2021. The data collection tool used was the scale of further study understanding. The data analysis technique used percentage descriptive analysis and Wilcoxon test. The descriptive results of the percentage showed that the understanding of further studies of students had increased by an average of 26,37%. Wilcoxon test analysis shows that tcount> ttable. Based on the results of the study, it can be concluded that the understanding of further studies has increased after being given group guidance with mind mapping techniques